DTN performance analysis of multi‐asset Mars‐Earth communications. (26th August 2019) - Alessi, Nicola; Caini, Carlo; de Cola, Tomaso; Martin, Sebastian; Mayer, Jeremy Pierce
Summary: The delay‐/disruption‐tolerant networking (DTN) architecture is considered the key enabling technology for future space communications, as confirmed by the current standardization within CCSDS and the experiments carried out onboard the International Space Station. Despite the scientific community efforts to analyze DTN architecture performance, most of the studies have focused on individual protocols, or have considered simple test cases, thus missing a whole system view. To bridge these research gaps, this paper presents a comprehensive analysis of DTN performance in Mars‐Earth communications, considering a realistic and complex end‐to‐end scenario, where multiple assets and multiple data flows are involved, as envisioned for future space missions. To this end, a virtualized testbed based on ION software was used for an extensive emulation campaign, focusing particularly on Bundle and Licklider Protocol interaction with the CGR routing algorithm. Abstract : This study focused on the applicability of the delay‐tolerant networking (DTN) protocol architecture to a complex network setup, representative of space communications between Mars and Earth ground stations. The work analysed multi‐link connectivity in terms of direct‐to‐Earth links, support of Mars orbiters and European Data Relay Satellite (EDRS), with attention on the performance of bundle protocol (BP)/Licklider transmission protocol (LTP) as well as contact graph routing (CGR) routing protocol. The conducted simulation campaigns demonstrated the benefits offered by DTN in such a complex scenario and shed light into some important aspects of protocol configuration.